PREVALENSI TOKSOPLASMOSIS PADA SAPI BETINA DI KELOMPOK TERNAK HANDINI MUKTI KECAMATAN SEYEGAN DAN DI KELOMPOK TERNAK GUMARANG JAYA KECAMATAN BANTUL BERDASARKAN UJI SEROLOGIS - , AJENG TYAS LARASATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Quality of food is getting considerable attention in the modern era , especially of animal origin food sources such as meat and milk. Toxoplasmosis is one of the many zoonotic disease caused by the protozoan parasite called Toxoplasma gondii. This disease can infect humans from undercooked meat consumed and milk not under pasteurization. The research was conducted to find out the prevalence of toxoplasmosis in cows which in Handini Muktiâs farm district of Seyegan and Gumarang Jayaâs farm district of Bantul based serological tests.Sampel females in both regions used in this study were 18 serum cows from Mukti Handiniâs farm group at subdistrict Seyegan and 13 serum cows from Gumarang Jayaâs farm group at subdistrict Bantul . Samples were examined serologically by using Pastorex Toxo Â® . The results that the prevalence of toxoplasmosis in serum cowsfrom Handini Muktiâs farm in subdistrict Seyegan is 5.6 % and at Gumarang Jayaâs farm group in subdistrict Bantul is 7.7 % Keywords: Toxoplasmosis, serological tests, Pastorex Toxo Â®, cows.